An NMR and X-ray study of the structure of the azo coupling product of 4-dimethylaminopent-3-en-2-one and benzenediazonium-tetrafluoroborate - Simůnek, Petr; Bertolasi, Valerio; Lycka, Antonín; Machácek, Vladimir (Organic & biomolecular chemistry, 2003)
4-Dimethylaminopent-3-en-2-one reacts with two molecules of benzenediazonium-tetrafluoroborate to give compound 1. The structure of this compound was determined by means of X-ray analysis of its crystal and 1H, 13C and 15N NMR spectra of its solution in CDCl3. The molecule of this compound contains one azo group and one hydrazone group. The substance exists, both in crystal form and in solutions of concentrations above 0.1 mol l(-1), in the form of a dimer, in which the pair of molecules are bound by two hydrogen bonds N-H...N. On diluting the solution, the dimers decompose, the two forms being in an equilibrium that is rapid on the NMR time scale.
Keywords: Models, Molecular; teplota; Hydrazones; dusík; uhlík; chemické modely; Magnetic Resonance Spectroscopy; Crystallography, X-Ray; Borates; Boric Acids; krystalografie rentgenová; molekulární modely; diazoniové sloučeniny; magnetická rezonanční spektroskopie; Hydrogen; Diazonium Compounds; kyseliny borité; Nitrogen; boritany; Carbon; vodík; hydrazony; Temperature; Models, Chemical